Experimental study of the effect of dielectric materials on the decomposition of carbon dioxide in a dielectric barrier discharge. (22nd February 2023) - Liu, Chang-Yu; Wang, Hai-Xing; Wang, Chao; Meng, Xian; Huang, He-Ji; Cao, Jin-Wen; Sun, Su-Rong; Yan, Cong
Abstract: The low-temperature nonequilibrium characteristics of dielectric barrier discharge (DBD) make it an important candidate for the decomposition and conversion of CO2 . In this study, quartz, alumina and zirconia are selected as the dielectrics to investigate the effect of dielectric materials of planar DBD reactor on the discharge and conversion characteristics of CO2 . It is shown that under the same input power conditions, zirconia has the highest CO2 conversion rate when used as a dielectric, followed by alumina, and quartz has the lowest. Combined with the analysis of the measured electrical characteristics, it is shown that zirconia has the highest transferred charge, thus further increasing the discharge efficiency. Experimental results of the single dielectric barrier layer-metal mesh electrode reactor show that the CO2 discharge can operate in the lower power range and the CO2 conversion rate is higher than that of the double dielectric barrier layer reactor. Spectroscopic measurements show that the emission intensity of the discharge in the reactor with high relative permittivity materials is higher than that in the case of low relative permittivity materials, and the emission intensity of the single dielectric layer reactor is also higher than that in the case of the double dielectric layer reactor.